UPAYA PENINGKATAN HASIL BELAJAR PAI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS VA SDN 015 BULUH KASAP DUMAI TIMUR - Noviar Noviar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is caused by the learning process is still centered on the teacher with the dominant use of lecture method, so that students are less motivated in the learning process, students are less enthusiastic and not actively asked in the delivery of learning materials. This study aims to improve teacher skills and student activities so as to improve learning outcomes PAI students class VA SDN 015 Buluh Kasap Dumai Timur using STAD type cooperative learning model. This research is a classroom action research conducted in two cycles, this research was conducted in April 2014, the subject of this research is the students of VA SDN 015 Buluh Kasap Dumai Timur class with 25 people consist of male students 11 Persons and female students 14 Persons. Measuring tools used are teacher activity, student activity, learning outcomes, and mastery learning. The results showed that the average of teacher activity in the first cycle was 70.92% (Good). In the second cycle is 70.92% (Good). In the second cycle is 79.48% (Good). The average learning outcome in the first cycle was 56.92% (Enough). In the second cycle is 73.84% (good). Based on the results of the study can be collected that STAD type cooperative learning model can improve learning outcomes of PAI in students.